OBSERVATIONS ON SOME PHYSICO-CHEMICAL FEATURES OF THE CHILKA LAKE - Banerjee, A C; Choudhury, N C Roy (Indian Journal of Fisheries, 2011)
A STUDY of certain physico-chemical features of Chilka Lake was commenced by the Chilka Investigation Unit in April, 1957, with a view to understand the pattern of iish migration into and their movements within the lake; their concentration in different sections of the lake and to correlate, if possible, the fluctuations in the abundance of the different commercial species with the physico-chemical characters of the environment. The present paper delineates the observations made in this regard during the period April, 1957 to March, 1961.